Peran Kepala Sekolah dalam Mengintegrasikan Pendidikan Karakter dan Pendidikan Islam - Aqbil Daffa Siahaan; Rosdialena R; Ahmad Sabri (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study examines the role of school principals in integrating character education and Islamic education within school environments that are increasingly complex due to social change, technological development, and shifting societal values. Schools are not merely viewed as institutions for knowledge transfer, but also as strategic spaces for students’ moral and spiritual development. The research employs a library research method with a qualitative descriptive approach by analyzing relevant literature such as books, scientific journals, and previous studies, which are then examined using content analysis techniques. The findings indicate that school principals play a central role as policy directors, school culture builders, and the main drivers of value internalization in educational institutions. Teachers function as the primary implementers of value integration in classroom learning through modeling and instructional practices, while school culture serves as a key medium for sustained value habituation. The integration of these two concepts requires synergy among principal leadership, teacher competence, and a conducive school environment so that values are not only understood theoretically but also reflected in daily practice. The success of this integration largely depends on visionary and consistent leadership that is capable of adapting to external challenges such as social and digital influences.